Your misery is no longer my pleasure: Reduced schadenfreude in Huntington's disease families. (October 2016) - Baez, Sandra; Santamaría-García, Hernando; Orozco, Janni; Fittipaldi, Sol; García, Adolfo M.; Pino, Mariana; Ibáñez, Agustín
Abstract: Schadenfreude – pleasure at others' misfortunes – has been systematically related to ventral striatum activity. This brain region is affected early in individuals with manifest and pre-manifest Huntington's disease (HD). However, the experience of schadenfreude has not yet been investigated in HD. In this study, 21 manifest HD patients, 19 first-degree asymptomatic relatives, and 23 healthy controls performed an experimental task designed to trigger schadenfreude, envy (another social emotion acting as an affective control condition), and control situations. Both HD patients and first-degree relatives experienced lower schadenfreude in response to others' misfortunes, with no group differences in ratings of envy and control conditions. These results offer unprecedented evidence of a highly specific impairment in reward processing, extending previous reports in manifest and pre-manifest HD individuals. Moreover, these findings suggest that early striatal impairments may be related to reduced feelings of schadenfreude. In sum, our work contributes to the understanding of emotional impairments in early stages of HD, while shedding light on their neural correlates.